31. PSYCHOLOGICAL DISORDERS IN STUDENTS IN THE HEALTH SECTOR AT DAI NAM UNIVERSITY AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current state of psychological disorders in health students at Dai NamUniversity in 2022 and some related factors.Research method: Cross-sectional descriptive study conducted on 412 health students at Dai NamUniversity in 2022. Psychological disorders were measured using the PQH9 scale.Results: The rate of students with psychological disorders in the study was 54.4%. The rates of"feeling bad about yourself - or feeling worthless or have disappointed yourself or your family" and"Loss of appetite or overeating" everyday account for 11.1% and 10.6%. The rate of psychologicaldisorders is highest among single students without a partner (56.5%) and lowest among marriedstudents (12.5%). Medical students have the highest rate of psychological disorders, accounting for61.7%, and nursing students have the lowest rate, with 46.7%. Students with cell phone abuse andsleep disorders had significantly higher rates of psychological disorders. The above differences arestatistically significant with p < 0.05.Conclusion: The rate of psychological disorders in Health Science students is relatively high.Psychological disorders are related to relationship status, field of study, sleep disorders and smartphoneabuse. Therefore, there is a need for psychological support measures in health science students.
Keywords: Psychological disorders, health science students, students, Dai Nam University, PQH9.